The toxic avenger. - Spears, Rick (Comic book writer); Ditta, Umar; Chaw, Walter; Brandon, Ivan; Harvey, Janet, 1966-; Goonface, Jonas (Legendary Comics, LLC, 2025)
"Get ready to mop up mayhem! The toxic avenger graphic novel is bursting with exclusive stories that expand the wild, weird world of Tromaville like never before. This is the must-have, no-holds-barred continuation of Legendary Entertainment's The Toxic Avenger. Featuring brand-new characters, returning faces, and the legendary Toxie himself. Don't miss your chance to own a piece of toxic history!" -- Back cover.